2002
DOI: 10.1085/jgp.20028593
|View full text |Cite
|
Sign up to set email alerts
|

Current-dependent Block of Rabbit Sino-Atrial Node If Channels by Ivabradine

Abstract: “Funny” (f-) channels have a key role in generation of spontaneous activity of pacemaker cells and mediate autonomic control of cardiac rate; f-channels and the related neuronal h-channels are composed of hyperpolarization-activated, cyclic nucleotide–gated (HCN) channel subunits. We have investigated the block of f-channels of rabbit cardiac sino-atrial node cells by ivabradine, a novel heart rate-reducing agent. Ivabradine is an open-channel blocker; however, block is exerted preferentially when channels dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
199
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(243 citation statements)
references
References 62 publications
24
199
1
9
Order By: Relevance
“…It is interesting to observe that in the mice treated orally with ivabradine for 1 week, reduction in HR was detectable with ivabradine plasma level in the range of 0.01-0.04 mM. In vitro patch-clamp studies showed that the IC 50 for the I f blockade by ivabradine is 1.5-2.2 mM (Bois et al, 1996;Thollon et al, 1997;Bucchi et al, 2002).…”
Section: X-j Du Et Almentioning
confidence: 98%
See 2 more Smart Citations
“…It is interesting to observe that in the mice treated orally with ivabradine for 1 week, reduction in HR was detectable with ivabradine plasma level in the range of 0.01-0.04 mM. In vitro patch-clamp studies showed that the IC 50 for the I f blockade by ivabradine is 1.5-2.2 mM (Bois et al, 1996;Thollon et al, 1997;Bucchi et al, 2002).…”
Section: X-j Du Et Almentioning
confidence: 98%
“…It has been shown that I f current of sinoatrial node pacemaker cells is affected by adrenergic stimulation (DiFrancesco & Tortora, 1991) and that ivabradine is a usedependent I f current blocker (Bois et al, 1996;Bucchi et al, 2002). Therefore, it is expected that the efficacy of ivabradine on HR would be modulated by alterations in the sympathetic activity.…”
Section: X-j Du Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Ivabradine binds to the subfamily of hyperpolarization-activated, cyclic nucleotide 4 (HCN4) channels, which creates the I(f) current. It diffuses across the cellular membrane and binds intracellularly to the HCN4 channel when it is in its open state [25].…”
Section: Ivabradine Pharmacokinetic and Pharmacodynamic Propertiesmentioning
confidence: 99%
“…A standardised nomenclature for HCN channels has been proposed by the NC-IUPHAR subcommittee on voltage-gated ion channels (see Hofmann et al, 2005). et al, 1993) and ivabradine (Bucchi et al, 2002) have proven useful in identifying and studying functional HCN channels in native cells. Zatebradine and cilobradine are also useful blocking agents.…”
Section: Hyperpolarisation-activated Cyclic Nucleotide-gated (Hcn)mentioning
confidence: 99%